Pengaruh Harga dan Kualitas Produk Terhadap Minat Beli Petani Padi Pupuk Bersubsidi PT. Pupuk Kujang – Studi Kasus Pada (Kios-Kios) Di Wilayah Karawang Timur Th. 2022 - Amalia Fatimatuzahra; Evi Selvi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Limited Liability Company (PT) Pupuk Kujang is a subsidiary of BUMN in Indonesia, namely PT Pupuk Indonesia Holding Company PT Pupuk Kujang is a large company engaged in production, trading, service provision, transportation, and expeditions. PT Pupuk Kujang as one of the Fertilizer companies in the West Java area covering all areas in West Java. The problem of subsidized fertilizers in the market has always been the subject of discussion by the government. With the help of the subsidized fertilizer program by the government to make it easier for farmers who want to buy fertilizer or use fertilizer that has the best quality. In this study a test will be carried out to determine the effect of price and product quality on buying interest at stalls selling cleaver fertilizer products. The subsidized fertilizer program run by the government has a fairly cheap price compared to the original fertilizer price. Starting this year, there are only 2 fertilizers subsidized by the government, namely urea and NPK fertilizer. This year, the government will only limit 2 subsidized fertilizer products. The results of this study determine the satisfaction of farmers with subsidized fertilizers and are in accordance with what the farmers want.